Testing for uniformity of fit in regression - econometric case study - Pratschk, JL (Economic & Social Studies, 1971)
It is frequently necessary to test regression results for uniformity of fit - i.e. to test the randomness of the distribution of the error terms. Such a test is necessary because an indication of a systematic trend in the pattern of residuals would suggest that the regression equation fitted to the data did not properly reflect the curvature of, the true relationship between the variables regressed.
Keywords: Uniformity